Penggunaan Media Lidi dalam Meningkatkan Kemampuan Berhitung Penjumlahan dan Pengurangan Siswa Kelas 1 di SDN 1 Keruak - Lalu. A. Hery Qusyairi (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2024)
The study aims to know the application of stick media in counting addition and subtraction students in class 1 at SDN 1 Keruak, and to enhance the ability to count addition and subtraction students in 1st grade at SDN 1 Keruak using stick media. Study held 3 meetings. The type of research used is study action class (PTK). Represents something method research carried out by teachers inside his class Alone For repair practice learning and improving results Study student. Data collection techniques used in the study These are observations used to assess the process and results of Study students, and tests or exercises to measure the ability of students. Application of stick media in class 1 can be done with the method following: researcher gives material about addition and subtraction, the researcher explains and demonstrates How method solution questions addition and subtraction with assistance from stick media, and the researchers share students become a number of the group for do question addition and subtraction. Stick media is capable increase the ability to count addition and subtraction students so that achieve completeness in a way classic with a value of 94%, an average value of 78.5, and a percentage completeness individually of 80%. Research results pointed out that the use of stick media to count students is ok, results Study students using stick media show results learn more good than before using stick media. The success of the learning process completeness results Study mathematics in a way classic is ≥ 85% of students who get it value above KKM value.